Elders' Experiences During Return Visits to the Emergency Department: A Phenomenographic Study in Taiwan. Issue 4 (July 2017) - Han, Chin-Yen; Lin, Chun-Chih; Goopy, Suzanne; Hsiao, Ya-Chu; Barnard, Alan
Abstract : Background: Elders often experience multiple chronic diseases associated with frequent early return visits to emergency departments (EDs). There is limited knowledge of the experiences and concerns of elders during ED return visits. Objectives: The purpose of the research was to explore the experiences of elders during ED return visits, with a view toward identifying factors that contribute to return visits. Methods: The qualitative approach of phenomenography was used. Data were collected at one ED in a 3, 000-bed medical center in Taiwan. Inclusion criteria were aged 65 or above and return visits to the ED within 72 hours of discharge from an index ED visit. The seven steps of qualitative data analysis for a phenomenographic study were employed to develop understanding of participants' experiences. Results: Thirty return-visit elders were interviewed in 2014. Four categories of description were established from the participants' accounts. These were "being tricked by ED staff, " "doctor shopping, " "a sign of impending death, " and "feeling fatalistic." The outcome space of elders with early return visits to ED was characterized as "seeking the answer." Conclusion: Index ED visits are linked to return visits for Taiwanese elders through physiological, psychological, and social factors.